PENGEMBANGAN MEDIA FLASHCARD BERBASIS CERITA DONGENG “MALIN KUNDANG” BAGI SISWA SEKOLAH DASAR - Imam Fathoni; Mei Fita Asri Untari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education plays a crucial role in improving the quality and character of students. One factor influencing successful learning is the use of appropriate media. Observations in grade IV of SDN Sawah Besar 02 Semarang showed that some students had not yet achieved the Learning Objective Achievement Criteria (KKTP) of 85%. Low learning outcomes were influenced by the lack of engaging learning media, resulting in limited student understanding of thematic material. Interviews with homeroom teachers confirmed that learning media were needed to increase student motivation and interest in learning. This study aimed to develop Flashcard media based on the fairy tale "Malin Kundang" as an alternative thematic learning media to improve student learning outcomes. The method used was Research and Development (R&D) with the ADDIE model, which included the stages of analysis, design, development, implementation, and evaluation. Flashcard media were made using simple materials in the form of picture cards with questions on the back, making them attractive, easy to use, and able to stimulate learning activities. Preliminary studies indicated that the school did not yet have adequate learning media, and students were very enthusiastic about the use of visual media. The development of this flashcard media is expected to help improve students' conceptual understanding, motivation, and learning outcomes in thematic learning.